Design of Temperature Measurement and Data Acquisition System based on Virtual Instrument LabVIEW - Xingju Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The LabVIEW virtual instrument consists of three parts: data acquisition, data test and analysis, output display. System control part is realized on the LabVIEW platform, data collection, data processing, and data recording, alarm and historical data readback function. The system uses DSl8B20 to measure temperature. The paper present design of temperature measurement and data acquisition system based on virtual instrument LabVIEW. Finally, this paper realizes the temperature acquisition and detection system, which is a new type of intelligent. System hardware circuit design is using digital temperature sensor DS18B20, and experiments show that the proposed method has a good effect.